HPV 16 and its variants: minor genome variations make a big difference - Knebel Doeberitz, Magnus von (Journal of the National Cancer Institute, 2016)
Distinct types of the human papillomavirus family are among the strongest human carcinogens (World Health Organization class I carcinogen) ( 1 ). However, papil
Gesehen am 11.05.2020